Periodontal Management of Leukocyte Adhesion Deficiency Type-I with Photodynamic Therapy-A Case Report - Divyasree Nadakuditi; Gopinath Cheni; Sowmya Lahari Sekuri; Kishore Kumar Katuri (Journal of Clinical and Diagnostic Research, 2023)
Leukocyte Adhesion Deficiency type I (LAD-I) is a rare autosomal recessive disorder affecting the immune system which is characterised by defects in white blood cell integrin receptors leading to impaired adhesion and chemotaxis with increased susceptibility to recurrent infections, delayed wound healing, and periodontitis. A case of aggressive form of generalised periodontitis in a 19-year-old girl with LAD-I is presented in this case report. The medical diagnosis was made on the basis of characteristic clinical and laboratory findings suggestive of LAD, particularly the total absence of Cluster of Differentiation (CD)18, CD11a, CD11b, and CD11c which were determined by flow cytometry. After non surgical periodontal therapy, photodynamic therapy with Low Level Laser Therapy (LLT) was performed. After 3 months, reduced inflammatory signs and improved periodontal health was observed. This report highlights the importance of the differential diagnosis of severe immunodeficiency disorders. It also emphasises the joint role of medical and dental specialists to control oral infections and thereby preventing tooth loss.